Implementation Of Women Empowerment And Children Protection Program (Study On The Women And Children Protection Unit Of Bojonegoro Regency 2020) - Dahlia, Nelly (IDFoS Indonesia, 2021)
The emergence of gender inequality issue has become a serious problem in the country development, especially the distribution of social welfare. Various national efforts as outlined in the form of legitimacy aim to encourage the role, position and quality of women to be further increased, to realize gender equality, especially in Bojonegoro Regency. One of them is by involving women as one of the active stakeholders in dealing with issues related to gender, through the Women Empowerment program and child protection. The purpose of this research was to describe and analyze two problem formulations, they were: How was the implementation of the Women Empowerment and children protection program in the women and children protection unit of Bojonegoro Regency in 2020, which was described and analyzed using George Edward III’s Public Policy Implementation Model Theory as a starting point. measure the success of the establishment of the PPA Unit in the Women Empowerment and children protection program. The researcher used descriptive qualitative research method using purposive sampling technique. The data collection methods used interview techniques, observation, literature study and documentation. Then, data processing was carried out using the Miles and Huberman interactive model and triangulation. The results of this research indicated that the responsibility of Bojonegoro Regency government in supporting Gender Mainstream was evidenced by the existence of women empowerment and children protection programs through the task force for women and children protection that have been effectively implemented in the community. Basically, the services provided by members of the Satgas PPA in assisting the government in carrying out their duties to deal with problems of women and children had so far worked according to their main duties and functions. However, it had not been able to run optimally due to several variables that were not optimal in their application.